Effects of macrocyclic lactones on the reproductive parameters of engorged Rhipicephalus (Boophilus) microplus females detached from experimentally infested cattle - Lopes, Welber Daniel Zanetti [UNESP]; Teixeira, Weslen Fabricio Pires [UNESP]; de Matos, Lucas Vinicius Shigaki [UNESP]; Felippelli, Gustavo [UNESP]; Cruz, Breno Cayeiro [UNESP]; Maciel, Willian Giquelin [UNESP]; Buzzulini, Carolina [UNESP]; Fávero, Flávia Carolina [UNESP]; Soares, Vando Edésio [UNESP]; Oliveira, Gilson Pereira de [UNESP]; da Costa, Alvimar José [UNESP] (Elsevier, 2013)
The present study therefore assessed the deleterious effects of MLs (ivermectin, abamectin, doramectin and moxidectin) on the reproductive parameters of engorged Rhipicephalus (Boophilus) microplus females that naturally detached from experimentally infested cattle in two experiments. The following reproductive parameters of engorged female ticks were analyzed: female weight, egg mass weight, percentage of hatchability, percentage of reduction in oviposition, percentage of reduction in hatchability, reproductive efficiency and percent control/efficacy of formulations with respect to reproductive parameters. In the experiment I, statistical analysis of the data grouped into 5-days intervals revealed that pour-on application of abamectin (500. mcg/kg) had significantly (p≤. 0.05) reduced engorged female weight, egg mass weight and percent hatchability on days 6-15, 6-20 and 11-20 post-treatment (p. t.) compared to the respective data for detached and pre-selected engorged females in the control group. The abamectin, demonstrated 33.41% of reduction in oviposition, 6.77% in hatchability and abamectin efficacy was of 13.99%. In the experiment II, statistically significant reductions (p≥. 0.05) were observed in animals treated subcutaneous with ivermectin (630. mcg/kg), doramectin (700. mcg/kg) and moxidectin (1000. mcg/kg) relative to the control for days 6-40, 6-48 and 6-40 p. t., respectively. Ivermectin reduced hatchability only on days 16-20 p. t., whereas doramectin significantly reduced (p≤. 0.05) hatchability on days 6-10 and 16-35 p. t. For moxidectin, deleterious effects on hatchability were observed on days 16-35 p. t. The percent reductions in oviposition of engorged female ticks were 46.31%, 62.17% and 61.02% with ivermectin, doramectin and moxidectin treatments, respectively. The percent efficacy of the formulations on the reproductive parameters of engorged female ticks was 21.22% for ivermectin, 36.03% for doramectin and 35.45% for moxidectin. Among the MLs assessed, doramectin and moxidectin had the highest acaricidal efficacies and the most deleterious effects on the reproductive parameters of engorged R. (B.) microplus females. However, future studies will be necessary to assess the extent to which these effects, along with acaricidal activity, can be used to control the ectoparasite in cattle. © 2013 Elsevier Inc..
Keywords: Engorged females; Macrocyclic lactones; Reproductive parameters; Rhipicephalus (Boophilus) microplus; abamectin; doramectin; ivermectin; lactone derivative; macrocyclic compound; moxidectin; animal experiment; animal model; body weight; cattle disease; drug efficacy; egg laying; female; female genital system; hatchling; nonhuman; priority journal; urogenital system parameters